The wisdom of failure : how to learn the tough leadership lessons without paying the price - Weinzimmer, Laurence G.; McConoughey, Jim. (San Francisco : Jossey-Bass, 2013)
Offers advice for becoming a successful leader by learning from the mistakes of others--without paying the price of failure.
Includes bibliographical references and index.
Keywords: Leadership; Success in business; Business failures